Dissecting the genetic architecture of sunflower disc diameter using genome‐wide association study - Yavuz Delen; Ravi V. Mural; Semra Palali‐Delen; Gen Xu; James C. Schnable; Ismail Dweikat; Jinliang Yang (Plant Direct)
Abstract Sunflower (Helianthus annuus L.) plays an essential role in meeting the demand for edible oil worldwide. The yield of sunflower seeds encompasses several component traits, including the disc diameter. Over three consecutive years, 2019, 2020, and 2022, we assessed phenotypic variation in disc diameter across a diverse set of sunflower accessions (N = 342) in replicated field trials. Upon aggregating the phenotypic data from multiple years, we estimated the broad sense heritability (H2) of the disc diameter trait to be 0.88. A subset of N = 274 accessions was genotyped by using the tunable genotyping‐by‐sequencing (tGBS) method, resulting in 226,779 high‐quality SNPs. Using these SNPs and the disc diameter phenotype, we conducted a genome‐wide association study (GWAS) employing two statistical approaches: the mixed linear model (MLM) and the fixed and random model circulating probability unification (farmCPU). The MLM and farmCPU GWAS approaches identified 106 and 8 significant SNPs located close to 53 and 21 genes, respectively. The MLM analysis identified two significant peaks: a prominent signal on chromosome 10 and a relatively weaker signal on chromosome 16, both of which were also detected by farmCPU. The genetic loci associated with disc diameter, as well as the related candidate genes, present promising avenues for further functional validation and serve as a basis for sunflower oil yield improvement.